Sustainability of Public Green Open Spaces: Evaluation of Implementation Management in Alam Sutera Residential, South Tangerang, Banten - Yuslim, Silia; Seanders, Olivia; Indrawati, Etty (Jurnal Pembangunan Wilayah dan Kota, 2025)
Global warming and climate change have increased the need for green open space in urban areas to support environmental quality and urban sustainability. As a township, the Alam Sutera Residential Area is recognized as a pioneer of green living with a strong commitment to improving environmental quality and community well-being; however, the sustainability of its public green open spaces has not yet been fully realized due to limitations in management implementation. This condition indicates existing issues in the management of public green open space, which form the basis of this study. This study aims to evaluate the extent to which public green open space management in Alam Sutera supports sustainability using a quantitative descriptive-analytical approach. Data were collected through Likert-scale questionnaires distributed purposively to green space managers, professional landscape architects, academics, and public observers. The novelty of this study lies in an integrated evaluation framework that combines public green open space management stages with sustainable landscape design principles and site-specific landscape needs within a single assessment instrument. The results indicate that the sustainability of public green open space in Alam Sutera has not been optimally achieved, as all evaluated variables—Planning, Implementation, Operations and Maintenance, and Monitoring and Evaluation—have not reached the very good category, with Planning and Operations and Maintenance failing to meet the required sustainability criteria.